Determinant of Indonesian Banking Profitability: Case Study Dual Banking System - Achsani, Muhammad Nur Faaiz Fathah; Kassim, Salina (Universitas Muhammadiyah Yogyakarta, 2021)
Islamic banking is considered as the perfect alternative of the current conventional financial system.Â However, there is still a huge amount of criticisms in terms of its practice, with many claims that Islamic banking and finance simply replaces conventional banking terminology and offers near-identical services to its clients but at a higher cost. The objective of this study is to make a comparative empirical assessment on the determinants of profitability between the Islamic and conventional banks in Indonesia. The panel data regression is applied to analyze the relationship between profitability indicators and both industry and country level characteristics. As far as the author knows, only few studies compare the profitability of Indonesian Islamic banks and conventional banks, especially in using econometrics approach. From the empirical result in the combined model, it is known that conventional banks are more profitable than Islamic banks. Compared to the combined regression, there is no significant difference in terms of significance of the independent variables and its relationship with the dependent variable for the conventional bank regression. Conventional banks are more familiar for the community due to the long operation compared to Islamic banks. Socialization needs to be done with some approach starting from mosques and Islamic schools. The development of supporting industries such as halal industry and halal tourism are also important to increase the demand for Islamic banking product. Beside increasing the demand, efforts to increase the economics of scale is also important with various efforts such as merger or acquisition.